The Impact of the COVID-19 Pandemic on Maternal Mortality Rates in Indonesia: A Retrospective Cohort Study - Imanuel Simbolon; Louisa Istarini; Desiree Montesinos; Habiburrahman Said; Yi-Fen Huang (Sriwijaya Journal of Obstetrics and Gynecology, 2023)
Introduction: The COVID-19 pandemic has presented unprecedented challenges to healthcare systems worldwide. Early reports have indicated an increase in maternal mortality rates (MMR) in various settings. This study aims to investigate the impact of the COVID-19 pandemic on MMR in Indonesia, a populous country in Southeast Asia with a high MMR. Methods: A retrospective cohort study was conducted using data from the Indonesian Ministry of Health's Maternal Mortality Surveillance System (MMSS). The study population included all pregnant women who delivered in Indonesia between January 1st, 2018, and December 31st, 2022. Women were categorized into two groups: those who delivered before the pandemic (January 1st, 2018, to February 29th, 2020) and those who delivered during the pandemic (March 1st, 2020, to December 31st 2022). The primary outcome was maternal death. Multivariable logistic regression was used to assess the association between the pandemic period and maternal mortality, adjusting for potential confounders. Results: A total of 1,250,480 deliveries were included in the study. The MMR during the pandemic period was 155 per 100,000 live births, compared to 118 per 100,000 live births pre-pandemic. After adjusting for confounders such as maternal age, socioeconomic status, and access to healthcare, the pandemic period was independently associated with an increased risk of maternal mortality (adjusted odds ratio [aOR] = 1.32; 95% confidence interval [CI], 1.25-1.39). Conclusion: The COVID-19 pandemic was associated with a significant increase in MMR in Indonesia. This highlights the need for continued efforts to strengthen maternal healthcare systems and ensure access to quality care, especially during public health emergencies.